CHARACTERIZATION OF NUTRITION, ANTIOXIDANT PROPERTIES, AND TOXICITY OF PHYSALIS ANGULATA L. PLANT EXTRACT - ADE CHANDRA IWANSYAH; WAHIDIYANTI PUTRI JULIANTI; ROHMAH LUTHFIYANTIQ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This research was to characterize and compare the nutrition, total phenolics (TP) content, antioxidant activity, and toxicity of all part of Physalis angulata L. extract. Methods: The proximate, minerals, TP content, antioxidant activity, and toxicity of all parts of physalis, namely, stem bark extract of P. angulata L. (ESC), leaf extract of P. angulata L. (ELC), rind extract of P. angulata L. (ERC), unripe fruit extract of P. angulata L. (EUF), and ripe fruit extract of P. angulata L. (EFC), were analyzed. The TP content, total flavonoids (TF), and free radical scavenging activity of ethanolic extract are studied using Folin–Ciocalteu assay, aluminum chloride assay, and 1,1-diphenyl 2-picrylhydrazyl scavenging assay. Brine shrimp lethality bioassay (LC50) used to measure the toxicity of extract. Results: The physalis leaves extract (ELC) contains the highest total of phenolics (144.4 mg galiic acid equivalent/g), a total of flavonoids (33.33 mg quercetin equivalent/g), and antioxidant activity (96.97 μg/ml) followed by ERC>EFC>EUF>ESC. Based on the level toxicity of LC50, the ripe fruit extract of P. angulata (EFC) (924.18 μg/ml) valued as cytotoxic. Conclusion: The data of nutrition, antioxidant properties, and toxicity of all parts of P. angulata extract provide for functional food product uses.